Phát triển năng lực tìm hiểu và tham gia hoạt động kinh tế - xã hội cho học sinh qua môn Giáo dục công dân: Nghiên cứu tại thành phố Hà Nội - Nguyễn, Thị Xiêm (Tạp chí Giáo dục, 2025)
In alignment with the requirements of the 2018 General Education Program, the development of secondary students’ competencies in exploring and participating in socio-economic activities is identified as a critical objective. This aims to equip students with the skills necessary to adapt to the rapid transformations of contemporary society. Nguyen Du Junior high school, located in Dai Mo District, Hanoi, is situated in a rapidly urbanizing area, making it a representative context for investigating this issue. The study reveals that students demonstrate a relatively good awareness of the importance of socio-economic engagement. However, their ability to apply acquired knowledge in practical contexts remains limited. Moreover, the participation lacks proactivity and depth and extracurricular programs have not been implemented in a consistent and integrated manner. These findings underscore the necessity of developing a comprehensive strategy, which includes innovating teaching methodologies, diversifying experiential learning formats, and strengthening the collaboration among schools, families, and the broader community. Future research could further evaluate the effectiveness of the proposed solutions and expand the scope of investigation to other geographical areas, thereby contributing to a more comprehensive understanding of this issue